STRATEGI PENINGKATAN KOMPETENSI PERSONEL/PENYIDIK DI SATUAN KERJA SATRESKRIM POLRES BANTUL - Brimantoro Supriyadi; Suhartono Suhartono (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
This study aims to 1) Identify the factors that cause the competence of personnel/investigators in the Bantul Police Satreskrim not optimal. 2) Formulating strategies to improve the competence of personnel/investigators in the Bantul Police Satreskrim work unit. This research uses a descriptive qualitative approach. Based on the research results, it can be concluded that: 1) The factors that cause the competence of personnel/investigators at the Bantul Police Criminal Investigation Unit to be not optimal are the lack of personnel and the inaccuracy of the placement system at the Bantul Police Criminal Research Unit. 2) The strategy to increase the competence of personnel/investigators in the Bantul Police Satreskrim work unit is the aspect of skills related to the ability of teamwork, planning and organizing in completing their work; aspects of attitude related to personnel integrity.